Learning beyond the lecture hall: a journey into knowledge to National Archive of Malaysia Sarawak Branch / Suhaida Halamy - Halamy, Suhaida (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
In adherence to the collaborative teaching of the Foundation of Archives course (IMD313) this semester, Miss Nor Hayati Kassim and I have crafted an exciting academic visit for students from groups IM1105B and IM1105C. The destination of this educational excursion is the esteemed National Archive of Malaysia, Sarawak Branch. The mission is clear: move beyond theoretical learning and dive into the world of hands-on experience at the National Archive of Malaysia, Sarawak Branch. The archive's working environment becomes its own classroom, offering a firsthand look at how history is preserved and cherished. Amidst the shelves of documents, students will gain insight into the daily lives of those safeguarding our collective past. In this journey from theory to practice, Miss Nor Hayati Kassim and I extend an opportunity for students to break free from the lecture hall routine.